Agronomic Evaluation of Coated Urea to Reduce Ammonia Volatilization from Side‐dress Applications to Corn. Issue 1 (17th January 2013) - Hunter Frame, William; Alley, Marcus M.; Thomason, Wade; Whitehurst, Garnett; Whitehurst, Brooks; Campbell, Robert
Abstract : Urea has become the dominant synthetic nitrogen fertilizer used worldwide; however, surface application of urea based fertilizers can lead to significant volatilization losses. The objectives of this research were: (i) to compare the effect of urea with and without the urease inhibitor N‐(n‐butyl) thiophosphoric triamide (NBPT) on corn ear leaf N concentration and grain yield; and (ii) to compare the effect of sulfate salts as coatings with and without NBPT on N concentration in corn ear leaves and corn grain yield in field studies. Urea and Arborite Ag, NBPT, were applied at four N rates: 50, 100, 150, and 200 lb/N acre; and the other seven coated urea treatments were applied at 100 lb N/acre at V5‐V7. The N concentration in corn ear leaves was significantly increased using Arborite Ag at 5 out the 10 locations during the study at α = 0.1. Regression analyses to predict N concentration in corn ear leaves and grain yield with N rates were significant for all 10 locations for N in corn ear leaves and 9 out of 10 for grain yield; however, the analyses indicate the N rate used to compare coated treatments (100 lb N/acre) was too high to detect treatment differences.